Planning For Housing Development and Coastal Settlements Based on Environmental Carrying Capacity in Teluk Haru, Langkat Regency - Donni Febriansyah Saragih; Cut Nuraini; Abdi Sugiarto (CV. Doki Course and Training, 2026)
This study aims to analyze the existing conditions, constraints, and strategies for developing safe, comfortable, and sustainable housing in the coastal area of ​​Teluk Haru, Langkat Regency. The study used a descriptive qualitative approach, with data collection through participatory observation, in-depth interviews, and documentation. The results show that settlements in Teluk Haru still face significant challenges, including limited land, flood and abrasion risks, mangrove damage, community economic constraints, and suboptimal development coordination. Recommended development strategies include adaptive housing development, mangrove conservation, community empowerment, and integration of planning with spatial planning and public infrastructure policies. The role of the government and other stakeholders is crucial in realizing integrated and sustainable housing development. This research is expected to serve as a reference in formulating housing development policies in coastal areas that consider social, economic, and environmental balance.